A case study on Eri silk as an alternative to Mulberry silk - Yabut, Emilie Anne Austria
This is a descriptive study that compares mulberry silk and eri silk. Mulberry silk is the most common type of silk produced by the Bombyx mori. Eri is a fiber is produced by another type of silkworm, the Philosamia ricini. Eri silk production is different from mulberry because it is a short fiber while mulberry is filamentous. The study discussed how eri silk is being developed in the Philippines, its production processes and its performance as compared to mulberry silk in the production of silk fabric used in consumer items such shawls and table linen. The researcher employed a descriptive research design. It was comparative in nature since it discussed the differences of eri and mulberry silk. Data was mainly obtained from the Eri Silk Learning Center in Puerto Princesa, Palawan. Observation, interview guides and previously printed documents were used as instruments for data gathering. Cocoons and fiber from both mulberry and eri silk were observed for physical properties such as shape, color, fiber appearance and fabric drapability. The study is also exploratory in nature since the writer worked on an under researched area, and the study is aimed for a better understanding of eri culture. There are few written documents about the rearing of eri moths and there are even fewer books primarily dedicated to eri culture. It is hoped that the study will orient local manufacturers and strike up genuine interest in eri cultivation. The study revealed that eri silk has excellent draping qualities, a resistance to wrinkling, and is lightweight yet warm - very much like mulberry silk. The main difference is that eri silk is coarser and thicker but stronger. In terms of physical appearance, eri fiber appears ecru or cream, while mulberry silk is white. Eri silk rearing is more attuned to the tropical countries such as the Philippines, since production time is shortened and the eri worms are less prone to disease. The main source of food is the castor oil, or tangan-tangan which is abundant in the country and easier to grow than mulberry. The fabric has anti-bacterial properties because of its high absorption effects, which is the reason for their high demand in the colder countries in Europe and Asia. Eri silk and silk products have great potentials in both the local and foreign markets. There should be a continuous effort to develop an eri silk industry in the Philippines since the silk produced can be substituted for mulberry silk in the manufacture of shawls, sweaters, scarves, table linen, curtains and other hand woven materials of export quality. Further studies on the fiber should lead to the production of high fashion garments and combining eri silk with the country's indigenous materials such as banana, piña and abaca.